The transition of Industrial 4.0 and competitiveness within Malaysian banking sector / Nor Izhwana Hafilda Abdul Basir - Abdul Basir, Nor Izhwana Hafilda (2022)
The innovation and technology in the financial sector are undeniable in Industrial 4.0. It will need a continuous adaptation in the financial sector as it will improve its market position and increase competitiveness in this sector. The purpose of this study is to determine the effect of bank's investment on Artificial Intelligence (Al) Investment, bank performance, and bank size (SIZE). This force is further classified based on dual banking (Islamic and Conventional). The data of 30 financial institutions which are registered under Bank Negara Malaysia. Period of I I -Years and the panel data analyzed by using Ordinary Least Square (OLS) method. The findings revealed cost of technology adaptation, bank's performance and size have a connection toward bank's competitiveness. Thus, investment on technology in new era of financial industry is crucial to improve competitiveness in banking industry.